N- and L-Type Voltage-Gated Calcium Channels Mediate Fast Calcium Transients in Axonal Shafts of Mouse Peripheral Nerve - Barzan, Ruxandra; Pfeiffer, Friederike; Kukley, Maria (Frontiers in Cellular Neuroscience, 2016)
In the peripheral nervous system a vast number of axons are accommodated within fiber bundles that constitute peripheral nerves. A major function of peripheral axons is to propagate action potentials along their length, and hence they are equipped with Na+ and K+ channels, which ensure successful generation, conduction and termination of each action potential. However little is known about Ca2+ ion channels expressed along peripheral axons and their possible functional significance. The goal of the present study was to test whether voltage-gated Ca2+ channels (VGCCs) are present along peripheral nerve axons in situ and mediate rapid activity-dependent Ca2+ elevations under physiological circumstances. To address this question we used mouse sciatic nerve slices, Ca2+ indicator Oregon Green BAPTA-1, and 2-photon Ca2+ imaging in fast line scan mode (500 Hz). We report that transient increases in intra-axonal Ca2+ concentration take place along peripheral nerve axons in situ when axons are stimulated electrically with single pulses. Furthermore, we show for the first time that Ca2+ transients in peripheral nerves are fast, i.e. occur in a millisecond time-domain. Combining Ca2+ imaging and pharmacology with specific blockers of different VGCCs subtypes we demonstrate that Ca2+ transients in peripheral nerves are mediated mainly by N-type and L-type VGCCs. Discovery of fast Ca2+ entry into the axonal shafts through VGCCs in peripheral nerves suggests that Ca2+ may be involved in regulation of action potential propagation and/or properties in this system, or mediate neurotransmitter release along peripheral axons as it occurs in the optic nerve and white matter of the central nervous system.